2018
DOI: 10.24014/ijielt.v3i2.4844
|View full text |Cite
|
Sign up to set email alerts
|

Speaking Skill in Using Community Language Learning (Cll)

Abstract: The researcher applied Community Language Learning (CLL) in teaching speaking skill. The purpose of this research was to identify the effect of using Community Language Learning (CLL) Method towards speaking skill students who received the class instruction by using CLL than students who do not receive method at the second semester students of ABA Persada Bunda in Pekanbaru. The  design of the research was experimental design with the total number of population are 25 students from the second semester students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In addition, the students also establish their foreign language learning online by discussing with friends and practicing new English words to gap perform better in their language skills (Pichette, 2009). Moreover, students are enthusiastic to accommodate their knowledge by investigating the language first to understand the problems more uncomplicated and requisite the online application to learn speaking more efficiently and capably (Masbirran & Fauzi, 2018). Therefore, group metacognitive strategies are essential for students to understand communication happened and produced directly speaking English like a native speaker.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the students also establish their foreign language learning online by discussing with friends and practicing new English words to gap perform better in their language skills (Pichette, 2009). Moreover, students are enthusiastic to accommodate their knowledge by investigating the language first to understand the problems more uncomplicated and requisite the online application to learn speaking more efficiently and capably (Masbirran & Fauzi, 2018). Therefore, group metacognitive strategies are essential for students to understand communication happened and produced directly speaking English like a native speaker.…”
Section: Discussionmentioning
confidence: 99%
“…Some empirical studies showed that this approach can help the students in improving their speaking (Damayanti, 2021;Ibrahim. dkk, 2018;Masbiran & Fauzi, 2018). The focus of their study was to see the effect of CCL on students' anxiety, to find learning methods that were more…”
Section: Introductionmentioning
confidence: 99%